Controversies in Prostate Artery Embolization: Future Best Practice - Goyal, Piyush; Salem, Riad; Mouli, Samdeep K. (Seminars in Interventional Radiology, 2022)
Prevalence of lower urinary tract symptoms secondary to benign prostatic hyperplasia is correlated with age. Men seeking treatment options with a low side effect profile often turn to prostate artery embolization (PAE). PAE continues to be refined with advanced tools and optimized techniques. Nonetheless, there exist controversies in terms of best practices for the management of lower urinary track symptoms (LUTS) with PAE. These controversies are essential for medical progress. Herein we suggest best practices moving forward based on currently available data. Given extensive safety data, we recommend PAE be considered alongside medical management and as a precursor to surgery. Given demonstrated efficacy across gland sizes, PAE can be performed in a single session, ideally in a hybrid angio-CT suite, without preoperative cross-sectional imaging. PAE should be initially performed with 300- to 500-μm size particles, and instead consider exploring other particles and sizes for repeat PAE. Finally, PAE can also be considered as first-line option for recurrent disease given the efficacy and excellent safety profile. This article is not meant to purport a dogma, but rather to serve as a guide to the experienced practitioner in challenging his or her own biases when performing PAE.
Keywords: prostatic artery embolization; benign prostatic hypertrophy; International Prostate Symptom Score; transurethral prostatectomy; embolization